Epigallocatechin-3-gallate modulates anti-oxidant defense enzyme expression in murine submandibular and pancreatic exocrine gland cells and human HSG cells. (20th January 2014) - Dickinson, Douglas; DeRossi, Scott; Yu, Hongfang; Thomas, Cristina; Kragor, Chris; Paquin, Becky; Hahn, Emily; Ohno, Seiji; Yamamoto, Tetsuya; Hsu, Stephen
Abstract: Sjogren's syndrome (SS) and type-1 diabetes are prevalent autoimmune diseases in the USA. We reported previously that epigallocatechin-3-gallate (EGCG) prevented and delayed the onset of autoimmune disease in non-obese diabetic (NOD) mice, a model for both SS and type-1 diabetes. EGCG also normalized the levels of proteins related to DNA repair and anti-oxidant activity in NOD.B10.Sn-H2 mice, a model for primary SS, prior to disease onset. The current study examined the effect of EGCG on the expression of anti-oxidant enzymes in the submandibular salivary gland and the pancreas of NOD mice and cultured human salivary gland acinar cells. NOD mice consuming 0.2% EGCG daily dissolved in water showed higher protein levels of peroxiredoxin 6 (PRDX6), a major anti-oxidant defense protein, and catalase, while the untreated NOD mice exhibited significantly lowered levels of PRDX6. Similarly, pancreas samples from water-fed NOD mice were depleted in PRDX6 and superoxide dismutase, while EGCG-fed mice showed high levels of these anti-oxidant enzymes. In cultured HSG cells EGCG increased PRDX6 levels significantly, and this was inhibited by p38 and JNK inhibitors, suggesting that the EGCG-mediated increase in protective anti-oxidant capacity is regulated in part through mitogen-activated protein kinase pathway signaling. This mechanism may explain the higher levels of PRDX6 found in EGCG-fed NOD mice. These preclinical observations warrant future preclinical and clinical studies to determine whether EGCG or green tea polyphenols could be used in novel preventive and therapeutic approaches against autoimmune diseases and salivary dysfunction involving oxidative stress.